Mampukah Job Satisfaction Menjadi Mediator Organizational Culture dan Compensation dengan Employee Engagement? - Hanifah, Fika Fikrotul; Sunarjo, Wenti Ayu (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This research aims to determine the influence of organizational culture and compensation on employee engagement through job satisfaction as a moderator. The data collection technique uses a questionnaire. The population in this study was all employee of PT. TF with purposive sampling. The sample for this research was 32 respondents. Reasearch data analysis uses Structural Equation Model (SEM) based on Partial Least Square (PLS) using with SmartPLS 4.0 software. The results of this research showed that organtizational culture positive influence and significantly to employee engagement, whereas compensation nogative and not significantly influence employee engagement. Organtizational culture positive influence and significantly to job satisfaction. Compensation positive influence and significantly to employee engagement. Job satisfication positive significantly influence employee engagement. Job satisfaction is able to mediate the influence of organizational culture on employee engagement Job satisfaction is able to mediate the influence of compensation on employee engagement.